Increased Levels of Systolic Blood Pressure Within the Normal Range Are Associated With Significantly Elevated Risks of Nonalcoholic Fatty Liver Disease. Issue 19 (May 2015) - Wu, Sheng-Jie; Zou, Hai; Zhu, Gui-Qi; Wang, Li-Ren; Zhang, Qi; Shi, Ke-Qing; Han, Ji-Bo; Huang, Wei-Jian; Braddock, Martin; Chen, Yong-Ping; Zheng, Ming-Hua; Tarantino., Giovanni
<x xml:space="preserve">Abstract</x> Abstract A positive association between hypertension or high-normal blood pressure (BP) and risk of nonalcoholic fatty liver disease (NAFLD) is well-known; however, no data have been generated exploring the risk of NAFLD within the normal range of BP. We aimed to assess the association between normal systolic blood pressure (SBP) and risk of NAFLD. A total of 27, 769 subjects from 2 separate medical centers were included. Subjects were divided into 4 groups (G1 to G4) by SBP levels: G1: 90–99 mmHg, G2: 100–109 mmHg, G3: 110–119 mmHg, and G4: 120–129 mmHg. The prevalence, hazard ratios (HRs) and 95% confidence intervals (CIs) for NAFLD were calculated across each group, using the G1 as reference. Higher SBP was observed in subjects with NAFLD than those without NAFLD. The prevalence of NAFLD in a cross-sectional population from G1 to G4 was 6.1%, 13.6%, 19.6%, and 25.8%, respectively. The HRs for NAFLD in the longitudinal population were 2.17 (95% CI 1.60–2.93), 3.87 (95% CI 2.89–5.16), 5.81 (95% CI 4.32–7.81) for G2, G3, and G4, respectively. After adjusting for known confounding variables, HRs of G2 to G4 were 1.44 (95% CI 1.06–1.96), 1.94 (95% CI 1.44–2.61), 2.38 (95% CI 1.75–3.23), respectively. This is the first study to demonstrate that increased levels of SBP within the normal range are associated with significantly elevated risks of NAFLD, independent of other confounding factors.